2016
DOI: 10.1021/acsami.6b09575
|View full text |Cite
|
Sign up to set email alerts
|

Porous, Hyper-cross-linked, Three-Dimensional Polymer as Stable, High Rate Capability Electrode for Lithium-Ion Battery

Abstract: Organic materials containing active carbonyl groups have attracted considerable attention as electrodes in Li-ion batteries due to their reversible redox activity, ability to retain capacity, and, in addition, their ecofriendly nature. Introduction of porosity will help accommodate as well as store small ions and molecules reversibly. In the present work, we introduce a mesoporous triptycene-related, rigid network polymer with high specific surface area as an electrode material for rechargeable Li-ion battery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…[100] As shown in Figure 4f, PA-10, PA-11, and PA-12 have a cyclic or triangular 3D structure imide. [100] As shown in Figure 4f, PA-10, PA-11, and PA-12 have a cyclic or triangular 3D structure imide.…”
Section: Monomeric Aromatic Imidesmentioning
confidence: 96%
“…[100] As shown in Figure 4f, PA-10, PA-11, and PA-12 have a cyclic or triangular 3D structure imide. [100] As shown in Figure 4f, PA-10, PA-11, and PA-12 have a cyclic or triangular 3D structure imide.…”
Section: Monomeric Aromatic Imidesmentioning
confidence: 96%
“…Furthermore, thanks to alterable ultrahigh surface areas, PPM have been adopted for catalyst supports to increase the efficiency of chemical reactions [14,15] and for electrodes of lithium-ion battery to enhance the electrochemical performance. [16][17][18] PPM have also been exploited for energy storage devices, [19] fuel cells, [20] low-dielectric-constant materials, [21] photonic bandgap materials, [22,23] scaffolds for tissue engineering, [4] proton exchange membranes, [24,25] masks for nanopatterning or lithography, [26] antireflection coating, [27] and many other applications. In these high-value applications, the functionality, the reliability, and the durability of PPM crucially depend on the microstructural patterns resulting from different formation processes associated with diverse underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported a series triphenylamine based CMPs in LIBs with a high capacity of 97.6 mA h g −1 at 2000 mA g −1 . Mukherjee et al reported a 3D porous polymer containing carbonyl groups and obtained a high specific capacity of 1100 mA h g −1 at 50 mA g −1 for LIBs . Recently, we developed a series of thiophene‐based CMPs anode materials for LIBs, which exhibited high discharge capacity of 1215 mA h g −1 at 45 mA g −1 .…”
Section: Introductionmentioning
confidence: 99%